Assessment of Environmental and Operational Performance of Thermal Powerhouses in Pakistan by Employing Data Envelopment Analysis Technique (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, the operational and environmental efficiencies of twenty-one natural gas and eleven residual furnaceoil thermal powerhouses using DEA (Data Envelopment Analysis) are presented. In the computation of the operationalconduct, important generation factors are utilized as input, and fuel-cost/actual generation (Y) is taken an output in Model-01.At the same time, estimation of the performance of the environmental parameters such as gases discharged into atmosphere aretaken as yield in Model-02. DEA technique is the key tool used for the calculation of the relative performance of the policymaking units with various outputs and inputs. CRS/CCR (Constant Return to scale) and VRS/BCC (Variable Returns to scale)type models of DEA are applied in the analysis. Relationship among the score (Efficiency) and Output/Input variables areexamined. Based on the analytical results the four most efficient powerhouses for each model are identified and one with theworst performance is also recognized.